Design of a low‐profile, dual‐mode, dual‐port and single‐band antenna with very high isolation for wireless body area network applications - Salma Mirhadi; Zeinab Poorjalili; Nader Komjani (IET Microwaves, Antennas & Propagation, 2023)
Abstract In this study, a simple and compact antenna structure with dual‐port and dual‐mode operating in a single‐band is proposed for wireless body area network. This antenna is composed of a rectangular ring patch antenna, which is shorted in the outer edge to generate an omni‐azimuthal radiation pattern. This pattern is desired for the on‐body communication level. A substrate integrated waveguide cavity‐backed slot antenna is also located at the centre of the structure and provides the broadside radiation pattern desired for the off‐body communication level. The proposed antenna is fabricated and measured. The measured results are in good agreement with the simulated ones. The measured mutual coupling between two ports is less than −40 dB which is about 13.5 dB better than that of previous works.